2011
DOI: 10.1509/jmkg.75.1.109
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Firms Invest in Consumer Advertising with Limited Sales Response? A Shareholder Perspective

Abstract: Marketing managers increasingly recognize the need to measure and communicate the impact of their actions on shareholder returns. This study focuses on the shareholder value effects of pharmaceutical direct-to-consumer advertising (DTCA) and direct-to-physician (DTP) marketing efforts. Although DTCA has moderate effects on brand sales and market share, companies invest vast amounts of money in it. Relying on Kalman filtering, the authors develop a methodology to assess the effects from DTCA and DTP on three co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 64 publications
3
18
0
2
Order By: Relevance
“…The starting year of the sample is determined by the availability of advertising spending 7 See, for example, Rao and Bharadwaj (2008); ;Srinivasan, Pauwels, Silva-Risso, and Hanssens (2009);Joshi and Hanssens (2010) ;Osinga, Leeflang, Srinivasan, and Wieringa (2011).…”
Section: Firm Characteristicsmentioning
confidence: 99%
“…The starting year of the sample is determined by the availability of advertising spending 7 See, for example, Rao and Bharadwaj (2008); ;Srinivasan, Pauwels, Silva-Risso, and Hanssens (2009);Joshi and Hanssens (2010) ;Osinga, Leeflang, Srinivasan, and Wieringa (2011).…”
Section: Firm Characteristicsmentioning
confidence: 99%
“…More precisely, in a large meta-analysis of 58 studies on the effectiveness of pharmaceutical promotional investments across several therapeutic categories, Kremer et al (2008) found an average elasticity of 0.326 for detailing, 0.123 for direct-to-physician advertising, and only 0.073 for DTCA. Apart from their direct effect on sales, promotional efforts, such as DTCA, Total World Market, Constant $ using Q410 average exchange rates may bring positive effects on other performance variables like stock returns or systematic risk (Osinga et al 2011). However, I argue that now is the time to move beyond these channels (direct-to-physician marketing and DTCA) and actively explore new direct-to-patient channels.…”
Section: Marketing To Empowered Patientsmentioning
confidence: 97%
“…11 The academic literature on DTCA is extensive, and my goal here is to complement this literature with an overview of the effects of patient empowerment on DTCA, especially given the regulatory limitations of such communication. I refer the reader to excellent papers providing in-depth summaries of the literature on DTCA, such as Iizuka and Jin (2005), Kolsarici and Vakratsas (2010), Narayanan et al (2004) and Osinga et al (2011). 12 Available at http://www.ema.europa.eu.…”
Section: Firm-to-patient Communication Via Mass Mediamentioning
confidence: 99%
“…Under these circumstances, an increase in complaint level may not necessarily be harmful to company market value, given the savings generated by not fulfilling the specific needs of these customers. In the effort to reduce significant negative effects, it is important to verify whether the company, in promoting products and services, has not created excessive expectations that will lead to future dissatisfaction (Osinga et al, 2011). Consumers perceive the product value on the basis of what the company's promises are, thereby seeking satisfaction over the long term.…”
Section: The Non-linear Effect Of Complaintsmentioning
confidence: 99%
“…There has been a need to establish better metrics to measure how different marketing strategies affect a company's market value (Mintz & Currim, 2013;Srinivasan & Hanssens, 2009) and a growing trend has arisen where financial indicators are increasingly being applied to previous studies (Anderson, Fornell, & Mazvancheryl, 2004;Fang, Palmatier, & Steenkamp, 2008;Goldenberg et al, 2007;Luo & Homburg, 2008;Osinga, Leeflang, Srinivasan, & Wieringa, 2011). Lehman (2004) emphasizes that practitioners who want to be involved in the important decisions their businesses make should seek consistent links between strategies and financial indicators, in particular, those related to increasing shareholder value.…”
Section: Introductionmentioning
confidence: 99%